Upregulation of RND3 Affects Trophoblast Proliferation, Apoptosis, and Migration at the Maternal-Fetal Interface - Ma, Xiao-Ling; Li, Xiao; Tian, Fu-Ju; Zeng, Wei-Hong; Zhang, Jun; Mo, Hui-Qin; Qin, Shi; Sun, Li-Qun; Zhang, Yu-Chen; Zhang, Yan; Lin, Yi (Frontiers in Cell and Developmental Biology, 2020)
RND3/RhoE is a unique member of the Rnd subfamily, a distinct branch of the Rho family of proteins that bind, but do not hydrolyze GTP, and thus remains constitutively active upon expression without regulation by guanine nucleotide exchange factors and GTPase-activating proteins. However, its function in cytotrophoblasts at the maternal-fetal interface has not yet been clarified. In this study, we found that RND3 expression was significantly increased in trophoblasts from the villous tissues of patients with recurrent miscarriage (RM). RND3 inhibited proliferation and migration and promoted apoptosis in HTR-8/SVneo cells. Using dual-luciferase reporter and chromatin immunoprecipitation assays, we found that forkhead box D3 (FOXD3) is a key transcription factor that binds to the RND3 core promoter region and regulates RND3 expression. Here, FOXD3 expression was upregulated in the first-trimester cytotrophoblasts of patients with RM, which in turn mediated RND3 function, including inhibition of cell proliferation and migration and promotion of apoptosis. Further, we found that RND3 regulates trophoblast migration and proliferation via the RhoA-ROCK1 signaling pathway and inhibits apoptosis via ERK1/2 signaling. Taken together, our findings suggest that RND3 and FOXD3 may be involved in the pathogenesis of RM and may serve as potential therapeutic targets.